Критерий сохранения почти периодичности второй производной от почти периодической функции - Димитрова-Бурлаенко, Светлана Димова (Национальный технический университет "Харьковский политехнический институт", 2019)
Статья посвящена изучению связи между непрерывностью функции и ее второй производной, заданных на оси в некоторой топологии ℑ, которая слабее естественной топологии 0ℑ. Рассматриваются дважды дифференцируемые абстрактные непрерывные на оси в некоторой более слабой топологии (в частности почти автоморфные или почти периодические) функции со значениями в банаховом пространстве. В работе представлены критерии ℑ−непрерывности (почти периодичности, почти автоморфности) второй производной в зависимости от ℑ−непрерывности (почти периодичности, почти автоморфности) самой функции. Для первой производной предполагается только ее существование, обеспечивающее существование второй производной в естественной топологии на оси.

A question on preserving the continuity of a function in the given topology plays an important role in the theory of almost periodic and almost auto-morphic functions. As known, the almost periodic, almost automorphic functions are respectively uniformly continuous, compact continuous functions in some weaker topology ℑ than the natural topology 0ℑ defined on the numerical axis. The present work belongs to this field and is devoted to the study of the relationship between the continuity of a function and its second derivative, defined on an axis in a certain topology, which is weaker than the natural topology. We consider a twice-differentiable abstract continuous function on the axis in some weaker topology (in particular, an almost automorphic or almost periodic function) with values in a Banach space. This study presents the criteria of ℑ−continuity (almost periodicity, almost automorphicity) of the second derivative depending on ℑ−continuity (almost periodicity, almost automorphicity) of the function itself. If a function is continuous in a weaker topology, then the second derivative is continuous in this topology if and only if it is locally uniformly continuous. Let a continuous almost automorphic function be given and its second derivative exists for any shift and compact. If the second derivative of the limit shift is equal to the limit shift of the second derivative, then the first and second derivatives are continuous almost automorphic functions.
Criterion for preserving almost periodicity of the second derivative of an almost periodic function
Keywords: непрерывность; равномерная непрерывность; квазиравномерная непрерывность; компактность; continuity; uniform continuity; quasi-uniform continuity; compactness